Management of Intellectual Property Rights in academia: The Estonian and Swedish perspectives. (1st September 2014) - Kelli, Aleksei; Mets, Tõnis; Jonsson, Lars
The objective of this research paper is to assess the impact of intellectual property (IP) ownership regimes (professor's privilege vs institutional ownership) on the knowledge transfer and academia–industry collaboration. One of the aims is also to define the advantages and challenges of both ownership regimes and different reward policies. The article analyses IP management systems at Uppsala University and the University of Tartu. Management of IP rights is not a thing in itself and its functioning and effectiveness cannot be evaluated without understanding its objectives. The basic idea behind the establishment of IP management systems in academia is to support academia–industry collaboration, which should result in increased welfare in a country and region.